The microbiome of the dinoflagellate Prorocentrum cordatum in laboratory culture and its changes at higher temperatures - Sanchez-Garcia, Selene; Wang, Hui; Wagner-Döbler, Irene (Frontiers in Microbiology, 2022)
In the ocean, phytoplankton are dependent on communities of bacteria living in the phycosphere, a hot spot of metabolic and genetic exchange. Many types of interactions between phytoplankton and phycosphere bacteria have been shown, but it is unclear if the microbial communities associated with microalgae strains in culture collections are beneficial or harmful to the host strain. Here we studied the microbial communities associated to four strains of the dinoflagellate Prorocentrum cordatum that had been isolated from distant geographical locations and maintained in culture collection for hundreds of generations. Community composition was determined by 16S rRNA gene amplicon sequencing. The dinoflagellate host strain was the strongest parameter separating communities, while growth phase, lifestyle (particle-attached versus free-living) and temperature had only a modulating effect. Although the strains had been isolated from distant locations in the Atlantic and Pacific Ocean, 14 ASVs were shared among all strains, the most abundant ones being Glivibacter, Marivita, uncultivated Rhodobacteraceae, Marinobacter, Hyphomonadaceae, Cupriavidus, Variovorax and Paucibacter. Adaptation to higher temperatures resulted in specific changes in each phycosphere microbiome, including increased abundance of rare community members. We then compared the growth of the four xenic cultures to that of the axenic P. cordatum CCMP1329. At 20°C, growth of the xenic cultures was similar or slower than that of CCMP1329. At 26°C, all four xenic cultures experienced a death phase, while the axenic culture stably remained in the stationary phase. At 30°C, only two of the xenic cultures were able to grow. A shift of dinoflagellate metabolism from autotrophy to mixotrophy and competition between dinoflagellate and bacteria for limiting nutrients, including essential vitamins may contribute to these differences in growth patterns.